ESG Integration in Commercial Real Estate: How is the Company Solving Integration Problem? - Adrian Pratama; Jerry Heikal (Management Analysis Journal, 2024)
The changing global trends and market dynamics are driving investors and banks to realize responsible investments by integrating environmental, social, and governance (ESG) principles as their reference. Commercial Real Estate (CRE) companies require funds for business development, acquisitions, and operations through investors and banks. This situation is compelling CRE companies to integrate ESG principles into their business activities as an obligation to meet responsible investment standards. This research aims to explore the initiatives of CRE companies in facing the problem of ESG integration. A qualitative research method with ethnographic approach was employed in this study to obtain in-depth information through observation and in-depth interviews with relevant informants. Observations were conducted at the NWP Property office in South Jakarta with three informants, including the Head of Research and ESG, a Supervisor of the Energy and Sustainable team, and Head of Operations at all malls owned by NWP Property. Based on the research findings, the main problem faced by the company in the integration process is dominated by the availability of data. There are 5 shared values from respondents in addressing the question of how the company solving integration problems. These values include using a data-driven approach in decision-making, collaboration between departments to helps in the problem-solving process, the importance of understanding team members' perspectives to achieve common goals, and systematic preparation and planning resulting in solutions to the issues.